Commodified money and crustacean nations - Desai, Radhika (Karl Polanyi and twenty-first-century capitalism, 2020)
Though Polanyi referred to three distinct fictitious commodities, one, money, and the fate of the apex structure that commodified it, the gold standard, structured The Great Transformation’s narrative. Despite this centrality of money and its commodification to Polanyi’s masterwork, there is near-deafening silence in Polanyi scholarship on money as a fictitious commodity. This chapter ends it. It traces Polanyi’s understanding of fictitious commodities to its sources in classical political economy and explains how the near total dominance of the antithetical tradition of neoclassical economics obscures understanding. The chapter also argues that the resulting argument shared a great deal with the classical Marxist theories of imperialism and of uneven and combined development of previous decades, particularly their arguments about the centrality of powerful nation states to capitalism. It stresses another hitherto neglected aspect of Polanyi’s argument, that the double movement led to the emergence of ‘crustacean nations’. As such, the chapter argues, The Great Transformation contributes a great deal towards a new approach to understanding world affairs, geopolitical economy, which challenges Ricardian ‘universalist’ understandings and takes the ‘materiality of nations’ seriously. It, and Polanyi, are more relevant than ever in our ‘deglobalizing’ age of multi-polarity.
Keywords: Marxism; fictitious commodities; imperialism; money